Synthesis and evaluation of a molecularly imprinted polymer for selective adsorption and quantification of Acid Green 16 textile dye in water samples - Foguel, Marcos Vinicius [UNESP] (2017)
An alternative for determining environmental pollutants, like textile dyes, is the use of molecularly imprinted polymers (MIPs) as solid phase extraction (SPE) or as sensor recognition systems. MIPs are tailor-made artificial receptor sites in a polymer, which present good affinity and selectivity. This work shows the synthesis of MIPs for the Acid Green 16 (AG16) textile dye and the results of rebinding, selectivity and application of this MIP in water samples. MIP synthesis was performed using AG16 dye (template), 1-vinylimidazole (functional monomer), ethylene-glycol-dimethacrylate (cross-link), 2,2′-azobis(2-methylpropionitrile) (initiator) and methanol (solvent) by bulk synthesis. The imprinted polymer presented excellent rebinding of 83%, an imprinted factor of 6.91 and great selectivity in comparison with other textile dyes. Additionally, the MIP showed high efficiency in the extraction of this dye in water samples, presenting a recovery rate close to 100% and a better performance when compared to commercial SPE cartridges. Due to this excellent performance for AG16, the application of this MIP to determine dyes in different matrices of environmental importance is promising.